Electrodes for lithium secondary batteries

A lithium secondary battery electrode with layered active materials, featuring a higher large particle ratio on the surface, addresses conductivity and resistance issues, enhancing capacity and output characteristics.

JP7618335B2Active Publication Date: 2025-01-21LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022179749
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-04
Filing Date
2022-11-09
Publication Date
2025-01-21
Estimated Expiration
2040-04-02

AI Technical Summary

Technical Problem

Lithium secondary batteries face challenges in achieving high capacity and output characteristics due to insufficient conductivity and increased resistance resulting from high active material loading, which affects battery performance.

Method used

The electrode for lithium secondary batteries is designed with multiple active material layers, where the second layer has a higher ratio of larger particles than the first, optimizing the weight ratio of active materials to enhance conductivity and reduce resistance.

Benefits of technology

The electrode achieves high capacity and low resistance characteristics, suitable for lithium secondary batteries requiring high capacity and output, by using a bimodal particle size distribution in layered active materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618335000001
    Figure 0007618335000001
Patent Text Reader

Abstract

An electrode for a lithium secondary battery is provided. The present invention relates to an electrode for a lithium secondary battery that has a high content of active material, thereby realizing high capacity characteristics, and also has excellent resistance characteristics and output characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Application No. 10-2019-0039670 filed on April 4, 2019, and all contents disclosed in the documents of said Korean patent application are incorporated herein by reference.

[0002] The present invention relates to an electrode for a lithium secondary battery having excellent resistance characteristics and output characteristics. [Background technology]

[0003] Recently, with the increasing demand for electric vehicles (EVs), hybrid electric vehicles (HEVs), etc., there is a growing need for lithium secondary batteries with high energy density, high discharge voltage and output stability as a power source for these vehicles.

[0004] In order to realize high capacity characteristics of lithium secondary batteries, the electrode loading amount must be increased, and therefore the electrode active material content increases and the electrode thickness increases, which causes the electrode conductivity to be insufficient, resulting in a decrease in the electrode resistance and output characteristics, resulting in a decrease in battery performance.

[0005] Therefore, in order to realize high capacity and high output characteristics of lithium secondary batteries, it is necessary to develop an electrode for lithium secondary batteries that has a high loading capacity, excellent conductivity, low resistance, and excellent output characteristics. Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an electrode for a lithium secondary battery that has a high content of active material, thereby realizing high capacity characteristics, and also has excellent resistance characteristics and output characteristics. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention provides An electrode for a lithium secondary battery comprising: a current collector; a first active material layer formed on the current collector; and a second active material layer formed on the first active material layer, The first active material layer and the second active material layer contain, as active materials, active material A having a D50 particle size of 7 μm to 15 μm and active material B having a D50 particle size of 2 μm or more and less than 7 μm, the weight ratio of active material A to active material B contained in the first and second active material layers is different from each other, and the ratio of active material A in the second active material layer is higher than that in the first active material layer; The weight ratio of active material A:active material B in the second active material layer is greater than 70:30.

[0008] Here, the weight ratio of active material A:active material B in the first active material layer may be greater than 50:50 and equal to or less than 70:30, and the weight ratio of active material A:active material B in the second active material layer may be greater than 70:30 and equal to or less than 95:5.

[0009] Here, the weight ratio of active material A:active material B in the first active material layer may be 60:40 to 70:30, and the weight ratio of active material A:active material B in the second active material layer may be 80:20 to 90:10.

[0010] In one embodiment, the active material A may have a D50 particle size of 7 μm to 11 μm, and the active material B may have a D50 particle size of 2 μm to 6 μm.

[0011] In another embodiment, the active material A may have a D50 particle size of 8 μm to 10.5 μm, and the active material B may have a D50 particle size of 3.5 μm to 6 μm.

[0012] The active material A and the active material B may be the same or different positive electrode active materials.

[0013] Here, the positive electrode active material may be a lithium-manganese oxide, a lithium-cobalt oxide, a lithium-nickel oxide, a lithium-nickel-manganese oxide, a lithium-nickel-cobalt oxide, a lithium-manganese-cobalt oxide, a lithium-nickel-manganese-cobalt oxide, or a lithium-nickel-cobalt-transition metal (M) oxide (wherein M is one or more selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo).

[0014] In one embodiment, the active material A and the active material B are the same compound, and may be a lithium-nickel-manganese-cobalt oxide.

[0015] The loading deviation between the first and second active material layers may be 0% to 10%.

[0016] The loading amount of the first active material layer and the second active material layer is 12 to 16 mg / cm 2 may be also possible.

[0017] The first active material layer and the second active material layer may each have a thickness of 35 to 45 μm. Effect of the Invention

[0018] The electrode of the present invention has high capacity and excellent resistance characteristics and output characteristics, and can be suitably used in lithium secondary batteries that require high capacity and high output. [Brief description of the drawings]

[0019] [Figure 1] 1 shows the results of battery resistance tests for Examples 1-2 and Comparative Examples 1-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Since the present invention can be modified in various ways and has various forms, the following detailed description will be given by way of examples of specific embodiments, but it should be understood that the present invention is not limited to the specific disclosed forms, but includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.

[0021] The present invention will be described in detail below.

[0022] According to one embodiment of the present invention, An electrode for a lithium secondary battery comprising: a current collector; a first active material layer formed on the current collector; and a second active material layer formed on the first active material layer, The first active material layer and the second active material layer contain, as active materials, active material A having a D50 particle size of 7 μm to 15 μm and active material B having a D50 particle size of 2 μm or more and less than 7 μm, the weight ratio of active material A to active material B contained in the first and second active material layers is different from each other, and the ratio of active material A in the second active material layer is higher than that in the first active material layer; An electrode for a lithium secondary battery is provided, wherein the weight ratio of active material A:active material B in the second active material layer is greater than 70:30.

[0023] In this specification, particle size (Dn) refers to the particle size at n% by volume of the cumulative particle number distribution by particle size, which is obtained by accumulating the particle sizes in ascending order. That is, D50 is the particle size at the 50% point of the cumulative particle number distribution by particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution by particle size.

[0024] The Dn can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in diffraction pattern according to particle size when the particles pass through a laser beam, and calculate the particle size distribution. D10, D50, and D90 can be measured by calculating the particle diameters at 10%, 50%, and 90% of the cumulative particle number distribution according to particle size in the measuring device.

[0025] In the present invention, a bimodal active material in the form of a mixture of small and large particle diameter particles is used as the electrode active material, and the active material layer is configured in multiple layers with different ratios of small and large particle diameter active material in each layer, thereby reducing the resistance of the high capacity electrode and improving the output characteristics.

[0026] Specifically, the lithium secondary battery electrode of the present invention has a higher content of large particle size active material in the second active material layer on the electrode surface side farther from the current collector than in the first active material layer closer to the electrode current collector, and therefore can exhibit stable conductivity and low resistance even when the active material content is increased.

[0027] More specifically, the present invention includes a first active material layer formed on a current collector as an active material layer, and a second active material layer formed on the first active material layer, and the first active material layer and the second active material layer each include active material A and active material B having different D50 particle sizes.

[0028] The active material A is a relatively large particle size active material with a D50 particle size of 7 μm to 15 μm, and the active material B is a relatively small particle size active material with a D50 particle size of 2 μm or more and less than 7 μm. By using a mixture of large and small particle size active materials in this way, the packing density and power density can be improved, and the thickness of the electrode can be reduced, thereby maximizing the electrode energy density.

[0029] Here, if the D50 particle size of active material A is excessively large, exceeding 15 μm, there may be a problem of a decrease in energy density, and if the D50 particle size of active material B is excessively small, less than 2 μm, there may be a problem of poor life characteristics and storage characteristics due to an increase in resistance, so it is preferable to satisfy the above particle size range.

[0030] In one embodiment, the D50 particle size of active material A may be 7 μm to 11 μm, or 8 μm to 10.5 μm, and the D50 particle size of active material B may be in the range of 2 μm to 6 μm, or 3.5 μm to 6 μm. Here, the maximum particle size (D95) of active material A is preferably less than 12 μm, and the minimum particle size (D5) of active material B is preferably 2 μm or more.

[0031] If the D50 particle size deviation between the large particle size and small particle size active materials is too small, the effect of the packing density decreases, so it is preferable that the D50 particle size deviation between active material A and active material B is 4 μm or more, within the limits of the aforementioned respective D50 particle size ranges.

[0032] In the present invention, the weight ratio of active material A:active material B in the second active material layer is preferably more than 70:30, with the ratio of active material A being higher than active material B. When the ratio of large particle size active material is high in the electrode surface, i.e., the portion in contact with the electrolyte and the separator, the electrolyte can easily penetrate, improving ion conductivity and exhibiting an effect on output characteristics. In one embodiment, the weight ratio of active material A:active material B in the second active material layer may be more than 70:30 and not more than 95:5, or may be 80:20 to 90:10.

[0033] The first active material layer formed on the electrode current collector also preferably has a higher ratio of active material A than active material B. However, in order to realize the effects of the present invention, it is more preferable that the ratio of active material A in the first active material layer is lower than that in the second active material layer. Specifically, the weight ratio of active material A:active material B in the first active material layer may be more than 50:50 and not more than 70:30, or may be 60:40 to 70:30.

[0034] The total content of active material A and active material B in the first active material layer and the second active material layer is not particularly limited, but it may be 80% by weight or more, or 90% by weight or more, based on the total weight of each active material layer, while being 99% by weight or less, or 97% by weight or less in order to ensure high-capacity characteristics. Here, the total content of the active materials in the first active material layer and the second active material layer may be the same as or different from each other as long as the above range is satisfied.

[0035] The electrode for a lithium secondary battery of the present invention may be a positive electrode or a negative electrode depending on the active material used.

[0036] When the electrode for a lithium secondary battery of the present invention is a positive electrode, the active material A and the active material B may be the same or different types of positive electrode active materials.

[0037] As the positive electrode active material, compounds known in the art as compounds capable of reversible intercalation and deintercalation of lithium can be used without limitation. Specifically, the positive electrode active material may be a lithium composite metal oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium.

[0038] Examples of the lithium composite metal oxide include lithium-manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (e.g., LiCoO2, etc.), lithium-nickel-based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese-based oxides (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), lithium-nickel-cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), lithium-manganese-cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1O4 (where 0 < Z1 < 2, etc.), lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc.), or lithium-nickel-cobalt-transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r3 M S2 )O2 (where M is one or more selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are atomic fractions of independent elements, 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, and p2 + q2 + r3 + s2 = 1), etc.), and one or any two or more of these compounds may be included.

[0039] Among these, in terms of being able to enhance the capacity characteristics and stability of the battery, the lithium composite metal oxide may be LiCoO2, LiMnO2, LiNiO2, lithium-nickel-manganese-cobalt oxide (e.g., Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, or Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), or lithium-nickel-cobalt-aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.).

[0040] In one embodiment of the present invention, the active materials A and B are the same type of compound as each other, and may be lithium-nickel-manganese-cobalt-based oxides. Lithium-nickel-manganese-cobalt-based oxides, also called NCM-based active materials, are preferably used because part of the expensive cobalt component is replaced by manganese, and they have high capacity characteristics and stability while being excellent in economy. Specifically, the active materials A and B are Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, or Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, where the D50 particle sizes of the active materials A and B with respect to each other satisfy the aforementioned range.

[0041] When the electrode for a lithium secondary battery of the present invention is an anode, the active materials A and B may be the same or different anode active materials as each other.

[0042] Compounds known in the art can be used without limitation as the anode active material. For example, crystalline carbon such as natural graphite and artificial graphite; soft carbon such as soft carbon, hard carbon, mesophase pitch carbide, and calcined coke; alloys of lithium with metals such as Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, or Sn; Si, SiO x (0 < x < 2), Si-C composites, Si-Q alloys (where Q is an alkali metal, alkaline earth metal, group 13-16 element, transition metal, rare earth element, or a combination thereof and is not Si), Sn, SnO2, Sn-C composites, Sn-R (where R is an alkali metal, alkaline earth metal, group 13-16 element, transition metal, rare earth element, or a combination thereof and is not Sn), and substances capable of doping and de-doping lithium, etc., but are not limited thereto.

[0043] In the electrode for a lithium secondary battery of the present invention, the loading amounts of the first active material layer and the second active material layer may be the same or different from each other. However, if the deviation in the loading amount is too large, it may be difficult to ensure the effect of the present invention, so that the deviation in the loading amount between the first active material layer and the second active material layer is preferably 0% to 10%, or 0% to 7%.

[0044] In order to achieve high capacity characteristics, the loading amounts of the first and second active material layers are each 12 to 16 mg / cm. 2 It may be a range.

[0045] Meanwhile, the thickness of the first active material layer and the second active material layer is preferably in the range of 35 to 45 μm, and the total thickness of the two active material layers is preferably 90 μm or less. If the total thickness of the electrode active material layers is excessively thick, exceeding 90 μm, it is difficult to control the increase in the resistance of the electrode, regardless of the adjustment of the mixing ratio of the large particle size and small particle size active materials in each layer, so it is preferable to satisfy the above range.

[0046] The first and second active material layers contain, in addition to the active materials described above, a conductive material and a binder.

[0047] The conductive material is used to impart conductivity to the electrodes, and any material can be used as long as it does not cause a chemical change in the constructed battery and is electronically conductive. Examples of the conductive material that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers of copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials containing mixtures of these.

[0048] The binder serves to adhere the active material particles to each other and to the current collector, and representative examples thereof include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.

[0049] The current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery. For example, the positive electrode current collector may be stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The negative electrode current collector may be copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloy.

[0050] The current collector may be in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven fabric, etc. The thickness of the current collector may be in the range of 3 to 500 μm, but is not limited thereto.

[0051] The method for manufacturing the electrode for a lithium secondary battery of the present invention is not particularly limited, but may be prepared by separately preparing a slurry for manufacturing a first active material layer and a slurry for manufacturing a second active material layer, sequentially applying the slurry to a current collector to form a first active material layer and a second active material layer, and then drying and rolling the resulting mixture. Such a manufacturing method may be embodied in the following examples.

[0052] The electrode for a lithium secondary battery of the present invention exhibits high capacity, low resistance and high output characteristics, and can be suitably used in lithium secondary batteries that require high capacity and high output. Thus, in one embodiment of the present invention, there is provided a lithium secondary battery including the electrode for a lithium secondary battery of the present invention.

[0053] The lithium secondary battery includes the lithium secondary battery electrode of the present invention as a positive electrode or a negative electrode, and also includes a separator and an electrolyte interposed between the positive electrode and the negative electrode.

[0054] The separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move, and may be any separator that is commonly used in lithium batteries. That is, a separator that has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability may be used. For example, the separator may be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and may be in the form of a non-woven fabric or a woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium ion batteries, and coated separators containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and may be used in a single layer or multi-layer structure.

[0055] The electrolyte may be an electrolytic solution containing a lithium salt and a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like, which is generally used in lithium secondary batteries.

[0056] The electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0057] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move.

[0058] The non-aqueous organic solvent may be a carbonate, ester, ether, ketone, alcohol, or aprotic solvent. The carbonate solvent may be dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc., and the ester solvent may be methyl acetate, ethyl acetate, n-propyl acetate, 1,1-dimethylethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. The ether solvent may be dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc., and the ketone solvent may be cyclohexanone, etc. The alcohol solvent may be ethyl alcohol, isopropyl alcohol, etc., and the aprotic solvent may be nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms and may contain a double bond oriented ring or ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, sulfolanes, etc.

[0059] The non-aqueous organic solvent may be used alone or in combination of two or more thereof. When two or more thereof are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which is widely understood by those skilled in the art.

[0060] In addition, in the case of the carbonate-based solvent, it is preferable to use a mixture of cyclic carbonate and chain carbonate in a volume ratio of about 1:1 to about 1:9, which has been shown to provide excellent electrolyte performance.

[0061] The non-aqueous organic solvent may further include the aromatic hydrocarbon organic solvent in addition to the carbonate solvent, wherein the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.

[0062] The non-aqueous electrolyte may further include a vinylene carbonate or ethylene carbonate based compound to improve battery life.

[0063] Representative examples of the ethylene carbonate-based compound include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, vinylene ethylene carbonate, etc. When the vinylene carbonate or the ethylene carbonate-based compound is further used, the amount of the vinylene carbonate or the ethylene carbonate-based compound used can be appropriately adjusted to improve the life span.

[0064] The lithium salt is a material that is dissolved in the non-aqueous organic solvent and acts as a lithium ion source in the battery to enable basic lithium secondary battery operation and promote the movement of lithium ions between the positive electrode and the negative electrode. Representative examples of the lithium salt include LiPF6, LiBF4, LiSbF6, LiAsF6, LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1Examples of the supporting electrolyte salt include lithium bis(oxalato)borate (LiBOB) and combinations thereof. The lithium salt is preferably used at a concentration within a range of 0.1 to 2.0M. If the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can be effectively transferred.

[0065] Examples of the organic solid electrolyte that can be used include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing secondary dissociation groups.

[0066] Examples of the inorganic solid electrolyte that can be used include nitrides, halides, and sulfates of Li, such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.

[0067] The lithium secondary battery of the embodiment can be used not only as a unit cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a number of battery cells. Furthermore, a battery pack including the battery module can be formed.

[0068] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present invention. Naturally, such changes and modifications fall within the scope of the appended claims.

[0069] [Example] In the following examples and comparative examples, the D50 of the active materials was measured using a laser diffraction method.

[0070] Specifically, 1 mg of the active material to be measured was dispersed in 30 g of distilled water, and then introduced into a laser diffraction particle size analyzer (Microtrac S3500) to measure the difference in diffraction pattern according to particle size when the particles pass through a laser beam, and calculate the particle size distribution. D50 was calculated by calculating the particle diameter at the point where the particle number cumulative distribution according to particle diameter in the analyzer is 50%.

[0071] Example 1 (1) Manufacturing of positive electrodes As the positive electrode active material A, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, and Li(Ni 0.6 Mn 0.2 Co 0.2 ) O2, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were used to manufacture a positive electrode in the following manner.

[0072] The positive active material A and the positive active material B were mixed in a weight ratio of 7:3, and the active material:conductive material:binder was mixed in a weight ratio of 97:1:2, and a slurry for a first active material layer was prepared using N-methylpyrrolidone (NMP) as a solvent.

[0073] In addition, the positive electrode active material A and the positive electrode active material B were mixed in a weight ratio of 9:1, and the active material:conductive material:binder was mixed in a weight ratio of 97:1:2, and a slurry for a second active material layer was prepared using N-methylpyrrolidone (NMP) as a solvent.

[0074] The slurry for the first active material layer was applied to the surface of an aluminum foil having a thickness of 12 μm at a rate of 14 mg / cm. 2 The slurry for the second active material layer was applied to the surface of the first active material layer at a loading amount of 14 mg / cm.2 The coating was dried at 120° C. for 10 minutes to form a second active material layer, and then roll pressing was performed to prepare a positive electrode.

[0075] (2) Manufacture of lithium secondary batteries The negative electrode active material was artificial graphite, the conductive material was carbon black, the thickener was carboxymethyl cellulose (CMC), and the binder was styrene-butadiene rubber (SBR). These were mixed in a weight ratio of 96:1:1:2 to prepare a negative electrode slurry.

[0076] The prepared negative electrode slurry was applied to a copper foil having a thickness of 8 um, dried at 100° C. for 10 minutes, and then roll-pressed to prepare a negative electrode.

[0077] Using the positive electrode and the negative electrode, a polyethylene separator (thickness 17 μm) was used as a separator, and an electrolyte (1 M lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC) / dimethyl carbonate (DMC) = 3 / 7 volume ratio) was injected to finally manufacture a lithium secondary battery in a coin full cell form.

[0078] Example 2 (1) Manufacturing of positive electrodes As the positive electrode active material A, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, and Li(Ni 0.6 Mn 0.2 Co 0.2 ) O2, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were used to manufacture a positive electrode in the following manner.

[0079] The positive active material A and the positive active material B were mixed in a weight ratio of 7:3, and the active material:conductive material:binder was mixed in a weight ratio of 97:1:2, and a slurry for a first active material layer was prepared using N-methylpyrrolidone (NMP) as a solvent.

[0080] In addition, the positive electrode active material A and the positive electrode active material B were mixed in a weight ratio of 9:1, and the active material:conductive material:binder was mixed in a weight ratio of 97:1:2, and a slurry for a second active material layer was prepared using N-methylpyrrolidone (NMP) as a solvent.

[0081] The slurry for the first active material layer was applied to the surface of an aluminum foil having a thickness of 12 μm at a rate of 14 mg / cm. 2 At the same time, the slurry for the second active material layer was applied to the surface of the first active material layer in a loading amount of 14 mg / cm. 2 The coating was dried at 120° C. for 10 minutes to form a second active material layer, and then roll pressing was performed to prepare a positive electrode.

[0082] (2) Manufacture of lithium secondary batteries A lithium secondary battery was manufactured in the same manner as in Example 1(2) using the same anode, separator, and electrolyte as in Example 1(2), except that the cathode manufactured in (1) above was used as the cathode.

[0083] Comparative Example 1 (1) Manufacturing of positive electrodes The slurry for the first active material layer of Example 1 was applied to the surface of an aluminum foil having a thickness of 12 μm at a rate of 28 mg / cm 2 After drying at 120° C. for 10 minutes, roll pressing was performed to prepare a positive electrode having a single active material layer.

[0084] (2) Manufacture of lithium secondary batteries A lithium secondary battery was manufactured in the same manner as in Example 1(2) using the same anode, separator, and electrolyte as in Example 1(2), except that the cathode manufactured in (1) above was used as the cathode.

[0085] Comparative Example 2 (1) Manufacturing of positive electrodes A positive electrode of Comparative Example 2 was manufactured in the same manner as in Example 1(1), except that a mixture of positive electrode active material A: positive electrode active material B = 5:5 (weight ratio) was used as the active material contained in the slurry for the second active material layer.

[0086] (2) Manufacture of lithium secondary batteries A lithium secondary battery was manufactured in the same manner as in Example 1(2) using the same anode, separator, and electrolyte as in Example 1(2), except that the cathode manufactured in (1) above was used as the cathode.

[0087] Comparative Example 3 (1) Manufacturing of positive electrodes A positive electrode of Comparative Example 3 was manufactured in the same manner as in Example 1(1), except that a mixture of positive electrode active material A: positive electrode active material B = 5:5 (weight ratio) was used as the active material contained in the slurry for the first active material layer, and a mixture of positive electrode active material A: positive electrode active material B = 7:3 (weight ratio) was used as the active material contained in the slurry for the second active material layer.

[0088] (2) Manufacture of lithium secondary batteries A lithium secondary battery was manufactured in the same manner as in Example 1(2) using the same anode, separator, and electrolyte as in Example 1(2), except that the cathode manufactured in (1) above was used as the cathode.

[0089] Experimental Example 1 The lithium secondary batteries manufactured in the respective Examples and Comparative Examples were evaluated for battery resistance characteristics at 25° C. using a charger / discharger capable of constant current / constant potential control.

[0090] Specifically, the operating conditions for each battery are as follows: Charging: 0.1C, CC (constant current) / CV (constant voltage), 4.3V, 0.005C cutoff Discharge: 0.1C, CC, 2.0V,

[0091] 1, it can be seen that, in Examples 1 and 2, the resistance was significantly reduced compared to Comparative Example 1, which was configured as a single layer, despite having the same loading amount. However, when the ratio of large particle size active material in the first active material layer was higher than that in the second active material layer, as in Comparative Example 2, no improvement in resistance was observed, and Comparative Example 3 showed an increase in resistance.

Claims

1. An electrode for a lithium secondary battery comprising a current collector, a first active material layer formed on the current collector, and a second active material layer formed on the first active material layer, The first active material layer and the second active material layer contain, as active materials, an active material A having a D50 particle size of 7 μm or more and 15 μm or less, and an active material B having a D50 particle size of 2 μm or more and less than 7 μm, The D50 particle size deviation between the active material A and the active material B is 4 μm or more within the range of the respective D50 particle size ranges, the weight ratios of active material A:active material B contained in the first active material layer and the second active material layer are different from each other, and the ratio of active material A in the above weight ratio of active material A contained in the second active material layer is higher than the ratio of active material A in the above weight ratio of active material A contained in the first active material layer; When the lithium secondary battery electrode is a positive electrode, the active material A and the active material B are each a lithium composite metal oxide containing cobalt, manganese, nickel, or one or more metals (excluding cobalt, manganese, and nickel) and lithium, When the electrode for a lithium secondary battery is a negative electrode, the active material A and the active material B are each selected from the group consisting of crystalline carbon, soft carbon, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn; Si, SiO x (0<x<2), Si-C complex, Si-Q alloy (Q is an alkali metal, an alkaline earth metal, an element of Groups 13 to 16, a transition metal, a rare earth element, or a combination thereof, and is not Si), Sn, SnO 2 , Sn—C complex, or Sn—R, where R is an alkali metal, an alkaline earth metal, a Group 13 to Group 16 element, a transition metal, a rare earth element, or a combination thereof, and is not Sn; The electrode for a lithium secondary battery, wherein the loading amount of each of the first active material layer and the second active material layer is 12 mg / cm 2 or more and 16 mg / cm 2 or less.

2. the weight ratio of active material A to active material B in the first active material layer is greater than 50:50 and less than or equal to 70:30; 2 . The electrode for a lithium secondary battery according to claim 1 , wherein a weight ratio of the active material A to the active material B in the second active material layer is greater than 70:30 and is not greater than 95:

5.

3. the weight ratio of the active material A to the active material B in the first active material layer is 60:40 or more and 70:30 or less; 2 . The electrode for a lithium secondary battery according to claim 1 , wherein a weight ratio of the active material A:active material B in the second active material layer is 80:20 or more and 90:10 or less.

4. 4. The electrode for a lithium secondary battery according to claim 1, wherein the active material A has a D50 particle size of 7 μm or more and 11 μm or less, and the active material B has a D50 particle size of 2 μm or more and 6 μm or less.

5. 4. The electrode for a lithium secondary battery according to claim 1, wherein the active material A has a D50 particle size of 8 μm or more and 10.5 μm or less, and the active material B has a D50 particle size of 3.5 μm or more and 6 μm or less.

6. The electrode for a lithium secondary battery according to claim 1 , wherein the active material A and the active material B are positive electrode active materials.

7. The positive electrode active material is LiMnO 2 , LiMn 2 O 4 , LiCoO 2 , LiNiO 2 , LiNi 1-Y Mn Y O 2 (where 0<y<1), LiMn 2-z Ni z O 4 (where 0<Z<2), LiNi 1-Y1 Co Y1 O 2 (where 0<Y1<1), LiCo 1-Y2 Mn Y2 O 2 (where 0<Y2<1), LiMn 2-Z1 Co Z1 O 4 (where 0<Z1<2), Li(Ni p Co q Mn r1 ) O 2 (where 0<p<1, 0<q<1, 0<r1<1, p+q+r1=1), Li(Ni p1 Co q1 Mn r2 ) O 4 (where 0<p1<2, 0<q1<2, 0<r2<2, p1+q1+r2=2) and Li(Ni p2 Co q2 Mn r3 M S2 ) O 2 (wherein M is one or more selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are each atomic fractions of independent elements, where 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1, and p2+q2+r3+s2=1).

8. The active material A and the active material B are Li(Ni p Co q Mn r1 ) O 2 (where 0<p<1, 0<q<1, 0<r1<1, p+q+r1=1) or Li(Ni p1 Co q1 Mn r2 ) O 4 7. The electrode for a lithium secondary battery according to claim 6, wherein p1 is 0<p1<2, 0<q1<2, 0<r2<2, and p1+q1+r2=2.

9. The electrode for a lithium secondary battery according to claim 1 , wherein a loading deviation between the first active material layer and the second active material layer is 0% or more and 10% or less.

10. An electrode for a lithium secondary battery comprising a current collector, a first active material layer formed on the current collector, and a second active material layer formed on the first active material layer, The first active material layer and the second active material layer contain, as active materials, an active material A having a D50 particle size of 7 μm or more and 15 μm or less, and an active material B having a D50 particle size of 2 μm or more and less than 7 μm, The D50 particle size deviation between the active material A and the active material B is 4 μm or more within the range of the respective D50 particle size ranges, the weight ratios of active material A:active material B contained in the first active material layer and the second active material layer are different from each other, and the ratio of active material A in the above weight ratio of active material A contained in the second active material layer is higher than the ratio of active material A in the above weight ratio of active material A contained in the first active material layer; When the lithium secondary battery electrode is a positive electrode, the active material A and the active material B are each a lithium composite metal oxide containing cobalt, manganese, nickel, or one or more metals (excluding cobalt, manganese, and nickel) and lithium, When the electrode for a lithium secondary battery is a negative electrode, the active material A and the active material B are each crystalline carbon, soft carbon, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn; Si, SiO x (0<x<2), a Si-C complex, a Si-Q alloy (wherein Q is an alkali metal, an alkaline earth metal, an element selected from Groups 13 to 16, a transition metal, a rare earth element, or a combination thereof, and is not Si), Sn, SnO 2 , a Sn-C complex, or Sn-R (wherein R is an alkali metal, an alkaline earth metal, an element selected from Groups 13 to 16, a transition metal, a rare earth element, or a combination thereof, and is not Sn); The electrode for a lithium secondary battery, wherein the first active material layer and the second active material layer each have a thickness of 35 μm or more and 45 μm or less.

Citation Information

Patent Citations

  • Multilayer anode having, in each layer, different amounts of binder and different active material grain size, and lithium secondary battery comprising same

    EP3399576A1

  • Cathode active materials for lithium-ion batteries

    US20170263929A1

  • Composite cathode active material, cathode and lithium battery containing the same, and method of preparing the composite cathode active material

    US20180145322A1

  • Positive electrode for secondary battery, and secondary battery

    WO2018221024A1